Molecular and Functional Evolution at the Odorant Receptor Or22 Locus in Drosophila melanogaster. (15th February 2019) - Shaw, Katherine H; Johnson, Travis K; Anderson, Alisha; de Bruyne, Marien; Warr, Coral G
Abstract: Insect odorant receptor ( Or ) genes determine the responses of sensory neurons that mediate critical behaviors. The Drosophila melanogaster Or22 locus represents an interesting example of molecular evolution, with high levels of sequence divergence and copy number variation between D. melanogaster and other Drosophila species, and a corresponding high level of variability in the responses of the neuron it controls, ab3A. However, the link between Or22 molecular and functional diversity has not been established. Here, we show that several naturally occurring Or22 variants generate major shifts in neuronal response properties. We determine the molecular changes that underpin these response shifts, one of which represents a chimeric gene variant previously suggested to be under natural selection. In addition, we show that several alternative molecular genetic mechanisms have evolved for ensuring that where there is more than one gene copy at this locus, only one functional receptor is generated. Our data thus provide a causal link between the striking levels of phenotypic neuronal response variation found in natural populations of D. melanogaster and genetic variation at the Or22 locus. Since neuronal responses govern animal behavior, we predict that Or22 may be a key player in underlying one or more olfactory-driven behaviors of significant adaptive importance.